Agrowisata Peternakan di Sragen (Penekanan Sustainable Architecture) - Ardi, Rully, Nur Rahmawati S, ST, MT (2016)
Agrotourism ranch is a livestock management as well as a means of educational tours in which there is involvement of the viewer to see, learn, and interact directly with farm animals. In addition there are means of supporting activities that are integrated with the tourist farms to produce products in the form of goods or services. Sragen is a county located in the border of Central Java and East Java. Sragen is an area that is relatively still beautiful with its vast open spaces and has the potential for development of livestock activities as well as potential of tourism. Environment tends to cool, low pollution levels and an adequate food supply could support the existence of farms as well as a tourist destination. Sustainable Architecture applied in planning agrotourism ranch as a design concept in order to prevent damage to the environment and resource management. Concept design of agrotourism ranch structuring both interior and exterior and the overall need to create welfare for farm animals and pleasure for visitors as well as friendly to the surrounding environment. Thus the sustainability of the activity and the existence of agrotourism ranch can survive and develop so as to provide benefits for society in general.